Diffusion Tensor Tractography Analysis of the Corpus Callosum Fibers in Amyotrophic Lateral Sclerosis - Kim, Jee-Eun (Korean Neurological Association, 2014)
BACKGROUND AND PURPOSE: Involvement of the corpus callosum (CC) is reported to be a consistent feature of amyotrophic lateral sclerosis (ALS). We examined the CC pathology using diffusion tensor tractography analysis to identify precisely which fiber bundles are involved in ALS. METHODS: Diffusion tensor imaging was performed in 14 sporadic ALS patients and 16 age-matched healthy controls. Whole brain tractography was performed using the multiple-region of interest (ROI) approach, and CC fiber bundles were extracted in two ways based on functional and structural relevance: (i) cortical ROI selection based on Brodmann areas (BAs), and (ii) the sulcal-gyral pattern of cortical gray matter using FreeSurfer software, respectively. RESULTS: The mean fractional anisotropy (FA) values of the CC fibers interconnecting the primary motor (BA4), supplementary motor (BA6), and dorsolateral prefrontal cortex (BA9/46) were significantly lower in ALS patients than in controls, whereas those of the primary sensory cortex (BA1, BA2, BA3), Broca's area (BA44/45), and the orbitofrontal cortex (BA11/47) did not differ significantly between the two groups. The FreeSurfer ROI approach revealed a very similar pattern of abnormalities. In addition, a significant correlation was found between the mean FA value of the CC fibers interconnecting the primary motor area and disease severity, as assessed using the revised Amyotrophic Lateral Sclerosis Functional Rating Scale, and the clinical extent of upper motor neuron signs. CONCLUSIONS: Our findings suggest that there is some degree of selectivity or a gradient in the CC pathology in ALS. The CC fibers interconnecting the primary motor and dorsolateral prefrontal cortices may be preferentially involved in ALS.